Pencegahan Stunting Melalui Program "1 Hari 1 Telur" di Dusun Bonginge, Desa Sipodeceng - Devy Febrianti; Sunandar Said (Window of Community Dedication Journal, 2025)
Stunting is a serious public health issue with long-term impacts on child growth and development. In Bonginge Hamlet, Sipodeceng Village, stunting remains a major concern. Through community empowerment activities, provided education on the importance of animal-based protein and implemented the “1 Egg a Day” program for toddlers over an eight-day period. This initiative included education sessions, egg distribution, and monitoring of consumption outcomes. The results showed an increase in mothers’ knowledge of balanced nutrition and positive changes in family dietary patterns. This activity highlights the importance of participatory approaches and simple interventions in efforts to reduce stunting at the village level.